The student self-confidence profile in learning English for Mathematics with the Tiktok application - Sirniawati Sirniawati; Putik Rustika (Concept : Community Concern for English Pedagogy and Teaching, 2024)
Speaking is a mentally demanding task for a foreign language learner. One of the aspects that can lessen speaking anxiety is confidence. This research was conducted to expose mathematical students' confidence profiles when speaking using the TikTok application. To reveal the mathematical students' confidence profile, this research used the quantitative analysis research approach comprised of in-depth data analysis in the form of numbers. The data was obtained from the second-year Mathematics students who took English for Mathematics course.  The results show the variety of levels of confidence and the aspects of confidence possessed by the students. Teachers can take advantage of the students' confidence profile to improve their teaching. Keywords: English for mathematics; Self-confident; Speaking; TikTok Application